ORGANIZATION OF INTEGRATED LESSON PROCESSES IN PRIMARY GRADES, PRACTICAL IMPORTANCE OF INTERDISCIPLINARY INTEGRATION (American Journal of Interdisciplinary Research and Development, 2023)
In this article, it is mentioned about the methods of correct and regular implementation of interdisciplinary integration in the course of teaching elementary school students and conducting lessons in a more interesting and effective way. Positive results of integrated lesson processes, which are considered one of the foundations of pedagogical skills, are also mentioned.